2015
DOI: 10.5430/ijhe.v4n2p27
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Student Engagement: A Case Study Examining Two Cohorts of Students Attending a Post-1992 University in the United Kingdom

Abstract: Issues relating to student retention and student engagement remain high on the agendas of higher education institutions worldwide. This case study considers the factors that impact on student engagement within a sample of first year undergraduate sports students attending a post 1992 university in the West Midlands region of the United Kingdom. These participants had started their three-year degree courses at the beginning of either the 2011/12 or the 2012/13 academic years. It should be noted that this meant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 28 publications
1
32
0
Order By: Relevance
“…Astin (1999) points out that students who are engaged in their learning, spend time on academic activities, interact with teachers and peers, and are more likely to improve their academic performance and personal growth. Research on students' engagement has concluded that teacher-student interactions are the most significant factor related to satisfaction with college and academic performance (Astin, 1999;Groves, Sellars, Smith, & Barber, 2015). In fact, some studies show that students who perceive their teachers as available and interested in their learning are more likely to be engaged, motivated and satisfied with their educational experience (Groves et al, 2015;Richardson & Radloff, 2014).…”
Section: Benefits Of Teacher-student Interactions In Higher Educationmentioning
confidence: 99%
See 2 more Smart Citations
“…Astin (1999) points out that students who are engaged in their learning, spend time on academic activities, interact with teachers and peers, and are more likely to improve their academic performance and personal growth. Research on students' engagement has concluded that teacher-student interactions are the most significant factor related to satisfaction with college and academic performance (Astin, 1999;Groves, Sellars, Smith, & Barber, 2015). In fact, some studies show that students who perceive their teachers as available and interested in their learning are more likely to be engaged, motivated and satisfied with their educational experience (Groves et al, 2015;Richardson & Radloff, 2014).…”
Section: Benefits Of Teacher-student Interactions In Higher Educationmentioning
confidence: 99%
“…According to Astin (1999), students' physical and psychological dedication on educational activities indicates their engagement in the educational experience that can have a positive impact on other academic processes. In fact, Groves et al (2015) and Richardson and Radloff (2014) suggest that students' engagement is related to satisfaction with the educational experience, motivation, learning and retention. The findings of the current research suggest that promoting positive teacher and student interactions in the first year can make a real difference in students' levels of satisfaction with the educational experience and engagement with their studies.…”
Section: Academic Benefits Of Positive Teacher-student Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many factors that affect student engagement in classes. Interaction between teachers and students and teacher behaviors can significantly affect the engagement of students (Garci, 2008;Jang, Reeve & Deci, 2010;Russel & Slater, 2011;Groves, Sellars, Smith & Barber, 2015;DeVito, 2016). Especially, respectful professional relationships and interaction are seen as ways to improve student engagement in the classroom (Parsons & Taylor, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Other authors studied the engagement from students' perspective, and pointed out that students' preparation is positively connected with the frequency of engagement (Dallimore et al, 2010) [8] and student engagement can be affected by the modes of reflexivity and co-reflexivity (Kahn, 2014) [9]. In addition, the quality of student-teacher relationship was found to be the most important factor to promote engagement (Groves et al, 2015) [10]. Although previous studies have focused on student engagement in higher education, they are limited in some specific aspects.…”
Section: Introductionmentioning
confidence: 99%